High-Throughput Screening for Drugs That Inhibit Papain-Like Protease in SARS-CoV-2. (December 2020) - Smith, Emery; Davis-Gardner, Meredith E.; Garcia-Ordonez, Ruben D.; Nguyen, Tu-Trinh; Hull, Mitchell; Chen, Emily; Baillargeon, Pierre; Scampavia, Louis; Strutzenberg, Timothy; Griffin, Patrick R.; Farzan, Michael; Spicer, Timothy P.
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in late 2019 has triggered an ongoing global pandemic whereby infection may result in a lethal severe pneumonia-like disease designated as coronavirus disease 2019 (COVID-19). To date, millions of confirmed cases and hundreds of thousands of deaths have been reported worldwide, and there are currently no medical countermeasures available to prevent or treat the disease. The purported development of a vaccine could require at least 1–4 years, while the typical timeline from hit finding to drug registration of an antiviral is >10 years. Thus, repositioning of known drugs can significantly accelerate the development and deployment of therapies for COVID-19. To identify therapeutics that can be repurposed as SARS-CoV-2 antivirals, we developed and initiated a high-throughput cell-based screen that incorporates the essential viral papain-like protease (PLpro) and its peptide cleavage site into a luciferase complementation assay to evaluate the efficacy of known drugs encompassing approximately 15, 000 clinical-stage or US Food and Drug Administration (FDA)-approved small molecules. Confirmed inhibitors were also tested to determine their cytotoxic properties. Here, we report the identification of four clinically relevant drugs that exhibit selective inhibition of the SARS-CoV-2 viral PLpro.